Efficacy of mechanical thrombectomy in patients with ischemic stroke and cancer. (September 2021) - Ciolli, L.; Bigliardi, G.; Ferraro, D.; Maffei, S.; Vandelli, L.; Dell'Acqua, ML.; Rosafio, F.; Picchetto, L.; Laterza, D.; Vincenzi, C.; Meletti, S.; Vallone, S.; et al.
Highlights: Similar recanalization rate is achieved in patients with and without cancer. Active cancer is associated with higher mortality in stroke patients. Independency is possible in patients with cancer with successful thrombectomy. Patients with stroke and previous cancer or without cancer have similar outcome. Abstract: Cancer-related coagulopathy is a known cause of stroke and can lead to formation of thrombi with a unique composition. The effectiveness of mechanical thrombectomy in cancer patients is still unknown. The aim of the study was to evaluate the rate of successful reperfusion and the clinical outcome in cancer patients with stroke treated with endovascular therapies, compared to patients without cancer. We performed a retrospective analysis of consecutive patients with ischemic stroke treated with endovascular therapies at our hospital between January 2008 and January 2016. A sub-group analysis was performed including only patients with cryptogenic stroke. We included in the final analysis 14 patients with active cancer and 267 patients without cancer. Successful reperfusion was achieved in 79% of patients without cancer, and 71% of patients with active cancer (P = 0.68). Patients with cryptogenic stroke and active cancer had a lower reperfusion rate compared to patients with cryptogenic stroke without active cancer, although not significantly so (2/4 cancer patients, 50% vs 37/50, 74%, p: 0.31). Mortality rate was higher among cancer patients. Hemorrhagic transformation occurred in similar proportions in the two groups. Endovascular treatment in cancer patients seems, thus, effective.